Cognitive Assessment as an Approach to Strengthening Flood Disaster Preparedness among adolescents - Hesti Kusumaningrum; Tetty Oktavia Limbong; Risma Aulia (JOURNAL EDUCATIONAL OF NURSING(JEN), 2024)
A flood is one of the most frequent natural disasters in Indonesia and often causes significant social, environmental, and economic impacts. Adolescents are considered a vulnerable group during disasters; therefore, adequate knowledge is essential to improve their preparedness and response capacity. This study aimed to examine the relationship between knowledge of flood disasters and disaster preparedness among students at MTs At-Taqwa 11 Bekasi, Indonesia. A quantitative analytical study with a cross-sectional approach was conducted involving 55 students from grades VII–IX. Data were collected using validated questionnaires that measured respondents’ level of knowledge regarding flood disasters and their preparedness in facing flood events. Descriptive statistics were used to describe respondent characteristics, while the Chi-square test was applied to determine the association between knowledge and preparedness levels with a significance level of 0.05. The findings revealed that most respondents had a good level of knowledge (50.9%), and nearly half demonstrated a high level of preparedness (47.3%). Statistical analysis showed a significant relationship between knowledge and flood disaster preparedness (p = 0.003). Students with better knowledge tended to exhibit higher preparedness levels. These results indicate that disaster-related knowledge plays an important role in strengthening preparedness among adolescents. Enhancing disaster education programs in schools may contribute to improving students’ readiness and resilience in responding to flood disasters.